Supplemented creatine induces changes in human metabolism of thiocompounds and one- and two-carbon units - Navrátil, Tomáš; Kohlíková, Eva; Petr, Miroslav; Pelclová, Daniela; Heyrovský, Michael; Přistoupilová, Kamila (Physiological research, 2010)
The administration of creatine (5 g/day for one month) to 11 young active sportsmen affected their urinary excretion of creatine, creatinine, and thiodiglycolic acid (TDGA) as well as blood levels of homocysteine, vitamin B12 and folates. The probands were divided into four groups, according to the amount of creatine found in urine, and of folates and vitamin B12 determined in blood. The changes of folates and vitamin B12 were mutually reciprocal. Each group utilized CR as donor of one- and two-carbon (1C and 2C) units by means of homocysteine (HoCySH), folates, and vitamin B12, in different metabolic pathways. In 10 men the creatine administration was accompanied by an increase of HoCySH level in blood, while in the last man, with accidentally discovered hyperhomocysteinemia, the HoCySH level dropped by 50 %. Differences between initial and terminal TDGA levels indicate that creatine affects equilibria of redox processes. Creatinine excretion into urine changed in the dependence on the extent of metabolic disturbances.
Keywords: thioglykoláty; Vitamin B 12; kyselina listová; Biotransformation; Humans; kreatinin; kreatin; vitamin B 12; oxidace-redukce; homocystein; Folic Acid; mladý dospělý; dospělí; financování organizované; Financing, Organized; lidé; Biomarkers; Creatinine; Homocysteine; dietní proteiny; Thioglycolates; časové faktory; Creatine; Adult; biologické markery; Male; potravní doplňky; Dietary Supplements; Oxidation-Reduction; biotransformace; Young Adult; mužské pohlaví; Dietary Proteins; Time Factors